Классификация наземных мобильных роботов - Круглов, Александр Игоревич (НТУ "ХПИ", 2017)
В данной статье рассматриваются классификации мобильных робототехнических систем в зависимости от их среды и сферы применения, кинематики, класса, а также типа управления. Для наземных мобильных роботов также выделены подклассы, проведен анализ их преимуществ и недостатков. Проанализирован выбор типа управления в зависимости от среды применения робота. Результаты могут быть использованы для выбора или разработки собственной мобильной робототехнической системы.

The development of artificial intelligence technologies suggests a wide implementation of robotic systems in different branches of industry, infrastructure and human life. In this paper classification of mobile robotic systems is given depending on their application sphere and environment (in-door/outdoor), kinematics, class (aerial, ground, water or hybrid), control type, mass and size. Highlighted kinematics subclasses for ground mobile robots: wheeled, caterpillar, legged, biomorphic, composite and hybrid robots. Analyzed and shown their advantages and disadvantages such as speed and passability. Analyzed what control type to choose depending on robot sphere of appliance: from human - controlled to automated, semiautonomous and fully autonomous.
Ground mobile robots classification
Keywords: робототехнические системы; типы управления; сфера применения; среда применения; МР; robotic systems; types of control